GENIUS KIDS: Learn to Count through Games - Wan Amirah Najwa Wan Idris; Hanasrullah Halim; Haslina Hassan; Ismail Yusuf Panessai (International Journal of Multimedia and Recent Innovation, 2019)
The goal of learning to count addition, subtraction, multiplication and division can have a positive impact for student to play because it can attract student to prefer learn while playing. The motivations for the player to play the game are interesting and not bored because this game is concept education. The aim of this research is to help students learn and love mathematics well. The objective of this research is to train student to play while counting. Researcher use use a game maker to develop this game and adobe photoshop for design. Researcher use a game maker to develop this game and adobe photoshop for design. The first idea of this game is not to make a fire, but wants to make the player jump to touch a block that contains a question mark so that it will reveal either poison or medicine. If medicine, Ben has extra point but if poison, he must to answer the question again. However, the idea is further expanded to make the barrier because the game is only for children aged 12 and below. Problem software development when compile many error at the system and must to reduce unimportant views and display size resolution because of the many elements causing game maker to run. The suggestion for this game is screens need to be raised to attract children to plays.